Potential radiosensitive germline biomarkers in the testes of wild mice after the Fukushima accident - Syun Tokita; Ryo Nakayama; Yohei Fujishima; Valerie Swee Ting Goh; Donovan Anderson; Ippei Uemura; Hikari Ikema; Jin Shibata; Yoh Kinoshita; Yoshinaka Shimizu; Hisashi Shinoda; Jun Goto; et al. (FEBS Open Bio)
We investigated potential germline‐specific radiosensitive biomarkers in the testes of large Japanese field mice (Apodemus speciosus) exposed to low‐dose‐rate (LDR) radiation after the Fukushima accident. Fukushima wild mice testes were analysed via RNA‐sequencing to identify genes differentially expressed in the breeding and non‐breeding seasons when compared to controls. Results revealed significant changes during the breeding season, with Lsp1 showing a considerable upregulation, while Ptprk and Tspear exhibited significant reductions. Conversely, in the non‐breeding season, Fmo2 and Fmo2 (highly similar) were significantly upregulated in radiation‐exposed Fukushima mice. qPCR analysis results were consistent with transcriptome sequencing, detecting Lsp1 and Ptprk regulation in the testes of Fukushima mice. While differences in gene expression were observed, these do not imply any causal association between the identified biomarkers and chronic LDR exposure, as other factors such as the environment and developmental age may contribute. This study provides valuable insights into the reproductive biology is affected by environmental radiation and highlights the value of assessing the effects of chronic LDR radiation exposure on testicular health in wild mice.